An examination of secondary school students' levels of reader self-perception ın terms of gender, grade, reading environment and frequency Ortaokul öğrencilerinin okur öz algı düzeylerinin cinsiyet, sınıf, okuma ortamı ve sıklığı açısından incelenmesi - Baştuğ, Muhammet; Çelik, Tuğba (Journal of Human Sciences, 2015)
This study aims to investigate secondary schools students' reader self-perception and its relationship with the variables gender, grade level, student’s and family's reading frequency and their preferences of reading environment. In the 2013-2014 academic year, a total of 549 students including the fifth, sixth seventh and eighth grade students were randomly selected from five schools in two different cities, located in the Central Anatolia region in this study. The scores of female students' levels of reader self-perception were higher than male students. Regarding the grade level, it was found that there is no statistically significant difference among grades in their levels of reader self-perception. With regards to reader self-perception level of the students in this research, the frequency of reading, and frequency of family reading differed statistically significantly. In addition, students who prefer online reading have higher scores of reader self-perception levels than those who prefer in print reading. Özet Bu araştırmada cinsiyet, okuma ortamı seçimi, sınıf düzeyi, öğrenci okuma sıklığı ile anne ve baba okuma sıklığı değişkenlerine göre öğrencilerdeki okur öz algı düzeylerini incelemek amaçlanmıştır. 2013-2014 eğitim yılında, 2 farklı ildeki 5 okuldan kolayda örnekleme yoluyla seçilen beşinci, altıncı, yedinci ve sekizinci sınıflara devam eden toplam 549 öğrenci katılmıştır. Araştırma sonuçlarına göre kız öğrencilerin okur öz algı düzeylerine ilişkin puanları, erkek öğrencilere göre daha yüksek çıkmıştır. Sınıf düzeyine göre öğrencilerin okur öz algı düzeylerine ilişkin puanlarında istatistiksel olarak anlamlı bir fark oluşmamıştır. Araştırmada öğrencilerin okur öz algı düzeyleri, öğrenci okuma sıklığı, öğrencinin anne ve baba okuma sıklığına göre okuma sıklığı yüksek olanlar lehine istatistiksel olarak anlamlı bir şekilde farklılaşmıştır. Ayrıca internet ortamından okuma yapmayı tercih eden öğrencilerin okur öz algı düzeylerine ilişkin puanları, basılı materyalden okuma yapmayı tercih eden öğrencilere göre anlamlı bir şekilde internet ortamından okuma yapanlar lehine farklılaşmıştır.